2015
DOI: 10.1007/s12011-015-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ultrastructural Changes in the Gill and Liver Tissue of Asian Sea Bass Lates calcarifer (Bloch) Exposed to Copper

Abstract: Surface ultrastructure of the gill and liver of 3-month-old Asian sea bass, Lates calcarifer, after copper exposure, was investigated by scanning electron microscopy (SEM). Fish samples were exposed to copper concentrations of 6.83 and 13.66 ppm (sublethal) for 28 days with parallel untreated control. These structures showed structural modifications in both low and high concentrations of copper exposure. Oedema, hyperplasia, desquamation, necrosis, epithelial lifting, lamellar fusion, collapsed secondary lamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…The SEM micrograph of gill in sodium arsenite treated Channa Punctatus (Figure 9) also reveals swelling and curling of secondary lamellae, complete fusion of secondary lamellae and surface wrinkling in numerous areas of the gill tissue. These observations are in accordance to those reported in Surface ultrastructural changes in the gill and liver tissue of Asian sea bass Lates calcarifes (Bloch) exposed to copper (Paruruckumani et al, 2015)…”
Section: Resultssupporting
confidence: 93%
“…The SEM micrograph of gill in sodium arsenite treated Channa Punctatus (Figure 9) also reveals swelling and curling of secondary lamellae, complete fusion of secondary lamellae and surface wrinkling in numerous areas of the gill tissue. These observations are in accordance to those reported in Surface ultrastructural changes in the gill and liver tissue of Asian sea bass Lates calcarifes (Bloch) exposed to copper (Paruruckumani et al, 2015)…”
Section: Resultssupporting
confidence: 93%
“…The morphological structure of the gills in fi sh has been demonstrated in previous studies by Scanning electron microscopy [31,32]. Paruruckumani, et al [33] determined the histopathological changes in the liver by SEM method with the detection of 2.5% glutaraldehyde and 1% osmium tetroxide in Lates calcarifer fi sh liver tissue. To demonstrate cell/tissue architectures by SEM in paraffi n block sections, Sawaguchi, et al ( 2018) examined rat organs from 30 μm thick paraffi n blocks on New Silane II-coated microscope slides.…”
Section: Discussionmentioning
confidence: 86%
“…Histopathologically, the disorganization of gill was the most frequently observed lesion in S. javus. It is suggested that such lesions are the consequence of a variety of water pollution problems (Cantanhêde et al, 2014;Paruruckumani et al, 2015). The appearance of lamellar aneurysm was also identified from all individuals.…”
Section: Discussionmentioning
confidence: 99%